OPTIMALISASI NALAR KRITIS SANTRI DALAM SISTEM BAHTSUL MASA'IL FIQHIYAH NU - Abdul Wasik (LP2M Universitas Ibrahimy, 2014)
In its development, is expected Bahtsul Masa'il using interpretive thinking on fiqh texts that exist, and the musyawirin demanded to know the rationale treasures-treasures that have become classic reference material Bahtsul Masa'il. Likewise, methodologically, thinking no longer confined Jurisprudence with reference to the text (qauli) alone, but must be balanced by optimizing methodologies, theories and principles used by priests schools. Or in other words with Jurisprudence not have to be text (qauli schools) but should prioritize contextual methodology (manhaj) with the Fiqh and Ushul Fiqh Rule-Rule